Cochlear implantation in children with auditory neuropathy: Lessons from Brown–Vialetto–Van Laere syndrome. (2nd January 2019) - Anderson, Phoebe; Schaefer, Simone; Henderson, Lise; Bruce, Iain A.
Abstract : Objective: Brown–Vialetto–Van Laere syndrome (BVVL) is a rare neurodegenerative disorder associated with auditory neuropathy (AN). The decision process for CI in AN is evolving with increasing evidence of efficacy. We evaluated the benefit of CI in children with BVVL syndrome. Methods: A retrospective study reviewed the pre- and post-operative hearing outcomes of three patients with BVVL who presented for CI. A fourth patient with BVVL who was not suitable for CI is also discussed. The primary outcomes were hearing thresholds and auditory perception. Outcome measurement instruments included visual reinforcement audiometry (VRA) or Play Audiometry (PA), Categories of Auditory Performance (CAP) and Auditory Speech Sound Evaluation (ASSE). Secondary outcomes were parental report (BAPP questionnaire), the perception of our SaLT and compliance. Results: Patient 1 had ASSE levels of 40–45 dB HL 1 year post-operatively, and CAP score had improved from 2 to 5. At 2-year review, aided thresholds were 40 dB at 2–4 kHz. Three months following CI, the CAP score of Patient 2 had improved from 3 to 5. At 6 months, thresholds were 25–30 dB at 2–4 kHz. Single words/phrases are used by both patients and benefit is reported by both families. Patient 3 has recently undergone CI, having been previously rejected at another centre. Three months following CI, his thresholds were 35–40 dB at 2–4 kHz and increased use of sign and vocalization is reported. Conclusion: CI in children with AN complicating BVVL has a variable, but a positive effect. Other manifestations of BVVL make measuring benefit challenging, in the absence of a 'bespoke' measurement instrument for children with complex needs. This study provides further evidence for the benefit of CI in children with AN.